(untitled) (Acta Entomologica Serbica, 2023)
Mosquito-borne diseases are considered major contributors to vector-borne diseases, threatening more than eighty per cent of the global population. Pest management depends on proper identification techniques. The barcode region of the cytochrome oxidase subunit I gene of mitochondrial DNA has recently been proposed as a systematic tool, functional in taxonomy and evolutionary study for species definition. This work is the first attempt to identify the main vector mosquito species from Bangladesh based on the MT-COI gene. Eleven vector mosquitos were identified. AT content (69%) was found to be higher than GC content (31%) at the COI barcode region of the mosquito. The interspecific genetic divergence range of medically important mosquitoes was 0.01-0.21. Haplotype analysis revealed that Mansonia annulifera diverged highly from its immediate ancestor by the highest mutational steps (59). Phylogenetic analysis indicated that species belonging to the same family were in the same major clade. Overall, our findings contribute to a better method of identifying major vector mosquito species by COI genes and for implementing management measures against mosquito pests in Bangladesh.